Evaluation of FLWA and SRAs on autogenous deformation and long-term drying shrinkage of high performance concrete. (30th August 2016) - Deboodt, Tyler; Fu, Tengfei; Ideker, Jason H.
Highlights: HPC mixtures (ternary blend) were examined for long-term drying shrinkage. Autogenous deformation of mortars was measured using a free deformation frame. FWLA was most effective in reducing autogenous shrinkage. FWLA showed limited benefit to the reduction of drying shrinkage. SRA was most effective in reducing long-term drying shrinkage. Abstract: The use of pre-wetted fine lightweight aggregate (FLWA) as partial replacement of normal weight fine aggregate has been shown to effectively reduce the deleterious effects of autogenous shrinkage in high performance concrete (HPC). In this study, autogenous deformation of mortar, free drying shrinkage of concrete prisms, and mechanical property development with various shrinkage mitigation methods were examined. HPC drying shrinkage specimens were externally wet cured for 14 days or less to commensurate with field curing. Three different methods were evaluated to provide a potential reduction in drying and autogenous shrinkage; pre-wetted FLWA, shrinkage-reducing admixtures (SRAs) or the combination of pre-wetted FLWA and SRA. It was observed that the combination of shale FLWA and SRA was the most effective at reducing autogenous deformation, and was 84% less than the control. HPC mixtures with SRA reduced the drying shrinkage by 17% at 1095 days of drying. Furthermore, extending the external wet cure beyond three days had little effect on the magnitude of drying shrinkage for all mixtures when compared to a control mixture cured for 14 days.